Light-driven transformation of biomass into chemicals using photocatalysts – Vistas and challenges - Sudhagar Pitchaimuthu (Journal of Environmental Management, 2021)
Lignocellulosic biomass has become an important sustainable resource for fuels, chemicals and energy. It is an attractive source for alternative fuels and green chemicals because it is non-edible and widely available in the planet in huge volumes. The use of biomass as starting material to produce fuels and chemicals leads to closed carbon cycle and promotes circular economy. Although there are many thermo-chemical methods such as pyrolysis, liquefaction and gasification close at hand for processing lignocellulosic biomass and transforming the derived compounds into valuable chemicals and fuels, the photocatalytic method is more advantageous as it utilizes light and ambient conditions for reforming the said compounds. Appraisal of recent literature indicates a variety of photocatalytic systems involving different catalysts, reactors and conditions studied for this purpose. This article reviews the recent developments on the photocatalytic oxidation of biomass and its derivatives into value-added chemicals. The nature of the biomass and derived molecules, nature of the photocatalysts, efficiency of the photocatalysts in terms of conversion and selectivity, influence of reaction conditions and light sources, effect of additives and mechanistic pathways are discussed. Importance has been given also to discuss the complementary technologies that could be coupled with photocatalysis for better conversion of biomass and biomass-derived molecules to value-added chemicals. A summary of these aspects, conclusions and future prospects are given in the end.